(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study aimed to determine the financial strains experienced by sole proprietorships in the variety store industry. By identifying these challenges, the study seeks to help sole proprietors develop strategies to manage financial difficulties and improve business sustainability. The researchers used a quantitative approach with a survey questionnaire and cluster (sub-cluster) sampling to gather data. The study surveyed 50 selected sole proprietors who experience financial strain in the variety store industry. The findings highlight key financial concerns and their corresponding importance to business sustainability. Budgeting was identified as a crucial factor, with a mean score of 4.00, emphasizing the need for financial knowledge and skills. Competition was also a significant challenge, with the statement "Offer better quality to enhance customer satisfaction and build a brand reputation" receiving a mean score of 3.58. In terms of customer retention, the statement "Make it easy for customers to find what they are looking for" had a mean score of 3.42. Lastly, for supply management, the statement "Find local sources to save on transit times and costs, particularly for essential goods" received a mean score of 3.62. This study emphasizes the importance of budgeting, product quality, customer retention, and efficient supply management in mitigating financial strain. Business owners are encouraged to remain resilient, innovative, and adaptable to sustain their operations. Future researchers should further explore the significance of budgeting strategies to help small business owners reduce financial challenges and enhance their business stability.